Punctures in the Periphery. Show-Bix and the Media Conscious Practice of Per Højholt. - Søndergaard, Morten (Nordlit, 2007)
Around 1967 and onwards, Per Højholt (1923-2004) performs a series of punctures in the periphery of a small and self-conscious avant-garde in Denmark - experiments that combine most of the known art forms and genres in a still more active dialogue with new media and technology. One of the first things Højholt engaged himself in at the time was Show-Bix, which is best described as an artist group consisting of the photographer and visual artist Poul Ib Henriksen, composer Gunner Møller Pedersen, and Per Højholt (at the time described largely as a poet). The group was operative from 1968 and until 1971, a period during which it conducted a series of complex experiments involving an audience as well as a media consciousness which is quite unique in Denmark - perhaps even more so today. In fact, I claim that Show-Bix is the visible proof of a paradigmatic change in Per Højholt's artistic practice, as well as in the overall definition of the contemporary art scene.